ASHES, POTSHERDS, AND GRIEF: A BIBLICAL STUDY OF THE SYMBOL OF SUFFERING IN JOB 2:8 - Nari, Frazier (Sekolah Tinggi Teologi Aletheia, 2026)
This article explores the symbols of suffering in Job 2:8, namely ashes, potsherds, and grief as expressions of human suffering. The study aims to analyze the theological meaning of these symbols within the context of Job’s suffering and their implications for understanding God’s justice and human experience of suffering. The method used is a qualitative biblical exposition with a literature study approach, examining the original Hebrew text and its historical-cultural background. The findings show that ashes and potsherds function as tangible signs of sorrow and brokenness, while grief represents the deep emotional experience of suffering. Overall, these symbols convey a profound theological message about the human condition and God’s presence amid suffering. This article concludes that the symbolism in Job 2:8 invites readers to face suffering with honesty and faith, recognizing that suffering is part of the relationship between God and humanity that shapes spiritual resilience in hope.